2008
DOI: 10.1095/biolreprod.107.064394
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Circannual Cycles of Ovarian Activity and Changes in Prolactin and Melatonin Secretion in Wild and Domestic Female Sheep Maintained under a Long-Day Photoperiod1

Abstract: The present study examines the ovulatory activity of wild and domesticated ewes subjected to either a constant photoperiod of long days (16L:8D) or natural changes in daily photoperiod for 16 mo. The aim was to determine whether an endogenous reproductive rhythm controls seasonal reproductive activity in these sheep, and how the photoperiod might affect this. The effects of long-day photoperiods on long-term changes in prolactin and melatonin secretion were also evaluated. The two species showed changes in rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 57 publications
2
40
0
2
Order By: Relevance
“…Teleb et al (2003) reported that PRL levels in Damascus goats were significantly higher during the non-breeding season (MarchMay) and tend to decrease as the breeding season (JuneNovember) approaches. An inverse relationship between PRL levels and reproductive activity in sheep and goats has also been reported by Gomez-Brunet et al (2008), Hesselink et al (1995), and Mori et al (1985). A significant increase in PRL levels following insertion and withdrawal of the intravaginal fluorogestone acetate sponges in all goat groups was demonstrated in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Teleb et al (2003) reported that PRL levels in Damascus goats were significantly higher during the non-breeding season (MarchMay) and tend to decrease as the breeding season (JuneNovember) approaches. An inverse relationship between PRL levels and reproductive activity in sheep and goats has also been reported by Gomez-Brunet et al (2008), Hesselink et al (1995), and Mori et al (1985). A significant increase in PRL levels following insertion and withdrawal of the intravaginal fluorogestone acetate sponges in all goat groups was demonstrated in this study.…”
Section: Discussionsupporting
confidence: 83%
“…It is a mixed breed resulting from crosses between various seasonal European breeds. It displays marked breeding seasons of about 6 month duration, with a circannual reproductive endogenous rhythm independent of food availability (Aguilar et al, 2001;Duarte et al, 2008), as reported in others breeds of sheep and goats from temperate latitudes (Gómez-Brunet et al, 2008;Karsch et al, 1989). Furthermore, it shows "classical" reproductive responses to short days and to long days, as well as existence of periods of refractoriness to long days and to short days (Delgadillo et al, 2011;Duarte et al, 2010), as in Saanen dairy goats (Gebbie et al, 1999).…”
Section: Accepted Manuscriptmentioning
confidence: 71%
“…This phenomenon is especially evident in seasonally breeding species. In sheep, the short day photoperiod, elevates plasma melatonin concentration which in turn leads to the inhibition in the secretion of PRL (Misztal et al, 1997;Morgan, 2000;Molik et al, 2007;Gomez-Brunet et al, 2008;Morgan and Hazlerigg, 2008;. Numerous data indicated that prolonged treatment with melatonin (i.e.…”
Section: Factors Inhibiting Prolactin Secretionmentioning
confidence: 99%